Combined disc pelletisation and thermal treatment of MSWI fly ash. (March 2018) - Huber, Florian; Herzel, Hannes; Adam, Christian; Mallow, Ole; Blasenbauer, Dominik; Fellner, Johann
Abstract: An environmentally friendly and cost efficient way for the management of municipal solid waste incineration (MSWI) fly ash represents its thermal co-treatment together with combustible waste. However, the safe introduction and storage of MSWI fly ash in the waste bunker is challenging and associated with severe problems (e.g. dust emissions, generation of undefined lumps and heat in case of moistened MSWI fly ash). Therefore, the aim of this study is to investigate the suitability of pelletisation as a pretreatment of MSWI fly ash. In particular, MSWI fly ash was characterised after sampling, pelletisation and thermal treatment and the transfer of constituents to secondary fly ash and flue gas was investigated. For this purpose, MSWI fly ash pellets with a water content of about 0.15 kg/kg and a diameter of about 8 mm have been produced by disc pelletiser and treated in an electrically heated pilot-scale rotary kiln at different temperatures, ranging from 450 °C to 1050 °C. The total contents of selected elements in the MSWI fly ash before and after thermal treatment and in the generated secondary fly ash have been analysed in order to understand the fate of each element. Furthermore, leachable contents of selected elements and total content of persistent organic pollutants of the thermally treated MSWI fly ash were determined. Due to the low total content of Hg (0.7 mg/kg) and the low leachate content of Pb (<0.36 mg/kg), even at the lowest treatment temperature of 450 °C, thermally treated MSWI fly ash pellets can be classified as non-hazardous waste. However, temperatures of at least 650 °C are necessary to decrease the toxic equivalency of PCDD/F and DL-PCB. The removal of toxic heavy metals like Cd and Pb is significantly improved at temperatures of 850 °C, 950 °C or even 1050 °C. The observed metal removal led to relatively high contents of e.g. Cu (up to 11, 000 mg/kg), Pb (up to 91, 000 mg/kg) and Zn (up to 21, 000 mg/kg) in the secondary fly ash. This metal enriched secondary fly ash might represent a potential raw material for metal recovery (e.g. via acidic leaching). Due to the high content of total dissolved solids observed in the leachate of thermally treated MSWI fly ash pellets, a wet extraction procedure is suggested to enable its safe disposal at non-hazardous waste landfills.